Guidance of an Autonomous Surface Vehicle for Underwater Navigation Aid - José Pedro Martins Pires e Sousa (2018)
Unmanned Underwater Vehicles (UUVs), such as Autonomous Underwater Vehicles (AUVs) and Remote Operated Vehicles (ROVs) are versatile tools, suitable for many activities in different fields. Besides the obvious scientific interest in ocean exploration by itself, UUVs can be useful in industrial applications such as monitoring underwater pipelines and communication lines and may also be used for military purposes. Even though their main advantage is avoiding risk to human lives, they also allow the simplification of missions' logistics and the reduction of their costs. The performance of any underwater vehicle in any given task is deeply affected by the precision of its localization system. The main challenge in underwater localization is the significant attenuation of any Radio Frequency (RF) signal underwater, which prevents the use of many common location methods such as the Global Positioning System (GPS). In order to overcome this difficulty, multiple localization techniques have been developed, based on different technologies. To increase the number of potential UUV applications, continued development and improvement of every subsystem is needed. The aforementioned localization system is one with much room for improvement, with new solutions frequently arising. Cooperative Navigation (CN) is one of these solutions. In CN, a UUV determines its position relatively to another vehicle that can determine its own position with certainty, like a surface vehicle equipped with GPS. This vehicle is called a Communication and Navigation Aid (CNA) vehicle. CN localization methods using only one support vehicle are appealing, to lower costs and logistics, but they require good positioning of the CNA vehicle to maintain observability and achieve good performances.The purpose of this dissertation is to develop a navigation system for a CNA surface vehicle. In a CN localization system, the UUV estimates its own pose with Dead Reckoning (DR) techniques and periodically obtains ranges from CNA vehicles to improve this estimate. The direction of the obtained ranges is particularly important, hence the need to adapt the surface vehicle's trajectory to the requirements of the UUV. The navigation system developed should be able to determine in real time the trajectory of the CNA that minimizes the position uncertainty of the UUV.